2010
DOI: 10.1051/0004-6361/200912841
|View full text |Cite
|
Sign up to set email alerts
|

Power halo and magnetic shadow in a solar quiet region observed in the Hαline

Abstract: Context. We investigate the oscillatory behavior of the quiet solar chromosphere and its discrete components in terms of oscillation properties, i.e. network and internetwork. For this purpose, we use a time series of high resolution filtergrams at five wavelengths along the Hα profile, obtained by the Dutch Open Telescope. Aims. We aim to gain insight on the distribution of power in different period bands and its variation between network and internetwork. Our spectral resolution provides information on the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 39 publications
9
35
0
Order By: Relevance
“…2001; McIntosh et al 2003;Moretti et al 2007;Vecchio et al 2007;Kontogiannis et al 2010bKontogiannis et al , 2014. Using Dutch Open Telescope Hα observations with a cadence of 30 s, Kontogiannis et al (2010aKontogiannis et al ( , 2010b pointed out that there is a strong possibility that power at longer time periods (∼7 minutes) may be enhanced as a result of the lifetimes of the mottles. Furthermore, Kontogiannis et al (2010a) also highlighted that the observed power enhancements, at both photospheric and chromospheric heights, may be closely related to the temporal dynamics of such transients and their lifetimes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2001; McIntosh et al 2003;Moretti et al 2007;Vecchio et al 2007;Kontogiannis et al 2010bKontogiannis et al , 2014. Using Dutch Open Telescope Hα observations with a cadence of 30 s, Kontogiannis et al (2010aKontogiannis et al ( , 2010b pointed out that there is a strong possibility that power at longer time periods (∼7 minutes) may be enhanced as a result of the lifetimes of the mottles. Furthermore, Kontogiannis et al (2010a) also highlighted that the observed power enhancements, at both photospheric and chromospheric heights, may be closely related to the temporal dynamics of such transients and their lifetimes.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging data from a passband centered at 0.7 Å from the Hα line core was used to produce the power maps where quiet-Sun "power halos" were positively identified (Kontogiannis et al 2010a(Kontogiannis et al , 2010b(Kontogiannis et al , 2014. This is closer to the Hα line core when compared to the predominantly photospheric bandpass at +0.9 Å.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of highresolution observations from ground-and space-based instruments, both standing and propagating SMAWs have been discovered in a multitude of structures in the solar atmosphere including magnetic pores (Morton et al 2011;Dorotovič et al 2014;Moreels et al 2015;Freij et al 2016), chromospheric network (Vecchio et al 2007; Kontogiannis et al 2010Kontogiannis et al , 2014, coronal loops (Wang et al 2015;Jess et al 2016), and polar plumes (Krishna Prasad et al 2011;Su 2014). Recent multiwavelength observations of sunspots reveal that umbral flashes (Beckers & Tallant 1969;Rouppe van der Voort et al 2003) and running penumbral waves (Giovanelli 1972;Bloomfield et al 2007;Freij et al 2014) observed in the chromosphere, and quasi-periodic propagating disturbances observed in the coronal loops (Berghmans & Clette 1999;De Moortel et al 2000;De Moortel 2009), are just different manifestations of the SMAWs that propagate from the photosphere through to the corona (Jess et al 2012a;Krishna Prasad et al 2015;Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%